2021
DOI: 10.3390/polym13213835
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Alcohol Polymer Functionalized Graphene Oxide Decorated with Gadolinium Oxide for Sequestration of Radionuclides from Aqueous Medium: Characterization, Mechanism, and Environmental Feasibility Studies

Abstract: Uranium (U(VI)) and thorium (Th(IV)) ions produced by the nuclear and mining industries cause water pollution, thereby harming the environment and human health. In this study, gadolinium oxide-decorated polyvinyl alcohol-graphene oxide composite (PGO–Gd) was developed using a simple hydrothermal process to treat U(VI) and Th(IV) ions in water. The developed material was structurally characterized by highly advanced spectroscopy and microscopy techniques. The effects of pH, equilibration time and temperature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Many techniques are used to remove heavy metals from aqueous solutions, including ion exchange, precipitation, adsorption, coagulation/flocculation, and reverse osmosis. Adsorption has proven to be the most successful method for removing heavy metals owing to its ease of use, practicability in the field, and low installation cost 4 , 5 . The adsorbent characteristics mostly determine the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques are used to remove heavy metals from aqueous solutions, including ion exchange, precipitation, adsorption, coagulation/flocculation, and reverse osmosis. Adsorption has proven to be the most successful method for removing heavy metals owing to its ease of use, practicability in the field, and low installation cost 4 , 5 . The adsorbent characteristics mostly determine the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…200 3.3.4 Other radionuclides. Apart from the above radionuclides, various graphene-bearing composites have recently been used to remove other radionuclides, such as Th(IV), [202][203][204][205][206] Am(III), 33 and Eu(III). 33,201 For instance, Huang et al reported on the high adsorption capacity (220 mg g −1 at pH 3.0) and selectivity (∼100%, Fig.…”
Section: Cs(i)mentioning
confidence: 99%
“…Graphene oxide (GO) and its composite-based adsorbents are excellent in adsorbing organic compounds, including organic dyes, as well as heavy metal ions [8][9][10][11][12][13][14]. GO is notable for its simpler fabrication and easier dispersion in water than other materials [15,16].…”
Section: Introductionmentioning
confidence: 99%